Peluang investasi dan strategi pengembangan usaha budidaya kutu lak (Laccifer lacca Kerr): studi kasus di KPH probolinggo, perum perhutani unit II jawa timur - Ira Taskirawati; F. Gunarman Suratmo; Dudung Darusman; Noor Farikhah Haneda (Jurnal Entomologi Indonesia, 2007)
Shellac flea Laccifer lacca Kerr is a phytophagous insect, which lives on kesambi tree (Schleichera oleosa Merr). During its life cycle, shellac flea secretes liquid known as LAK and has many uses, such as varnish/polish, food cover, drug capsule, cassette ribbon, etc. In 2005, Perum Perhutani produced 60,547 kg LAK pellets, but has not fulfilled market demand. Cultivation technique is still conducted in a very simple way. Investment in developing shellac flea is also profitable, and promising. There are two choices of management schemes in it cultivate, the first is by infecting shellac flea to the host tree when the tree is 15 years old  and the second is by infecting shellac flea when the tree is 4 years old. Financially, the latter approach is more beneficial than the former one. The value of NPV + 22 321 052 395, IRR 16.9%, BCR 1.55 and Net B/C 3.71 with discounted payback period for 10 year 8 months. SWOT analyzing was used in the design strategy as a management approach.